2017
DOI: 10.1016/j.watres.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and metagenomic analysis of an anammox bacterial enrichment related to Candidatus “Brocadia caroliniensis” in a full-scale glycerol-fed nitritation-denitritation separate centrate treatment process

Abstract: A distinctive red biofilm was observed in a glycerol-fed digester liquid effluent treatment process coupling partial nitrification (nitritation) and partial denitrification (denitritation) processes. Based on initial phylogenetic screening using 16S rRNA clone libraries and quantitative polymerase chain reaction, the biofilm was enriched in novel anaerobic ammonium oxidizing bacteria (AMX/anammox) closely related to Candidatus "Brocadia caroliniensis". The metabolic functionality of the C. "Brocadia carolinien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…B. caroliniensis utilize a nirK homologue or a novel nitrite reductase employing the conventional NO-dependent pathway for hydrazine production or possess the ability to switch to a NO-dependent pathway in the absence of nitrite. An alternate pathway for NO production through oxidation of hydroxylamine by a hydroxylamine oxidoreductase ( hao )-like protein was indeed detected by Park et al (14) and proposed that this alternate pathway could potentially be activated under nitrite limitation. NO was also shown to oxidize ammonium to dinitrogen gas under nitrite limitation in Ca .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…B. caroliniensis utilize a nirK homologue or a novel nitrite reductase employing the conventional NO-dependent pathway for hydrazine production or possess the ability to switch to a NO-dependent pathway in the absence of nitrite. An alternate pathway for NO production through oxidation of hydroxylamine by a hydroxylamine oxidoreductase ( hao )-like protein was indeed detected by Park et al (14) and proposed that this alternate pathway could potentially be activated under nitrite limitation. NO was also shown to oxidize ammonium to dinitrogen gas under nitrite limitation in Ca .…”
Section: Discussionmentioning
confidence: 91%
“…Metagenomic analysis revealed that Ca . B. caroliniensis have multiple copies of nitrite/formate transporters ( focA ) that provide a competitive advantage at low nitrite concentrations due to a low intrinsic nitrite affinity constant (14) . This could potentially help them scavenge nitrite from heterotrophic denitrifiers in the presence of organic carbon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations